(untitled) (Research, Society and Development, 2024)
This article aims to present a case report of a canine patient with first-degree atrioventricular block and occult ventricular pre-excitation. A 9-year-old male dog, was referred for cardiological evaluation for suspected heart failure. The physical examination revealed a regular heart rhythm, loud holosystolic murmur over the left apex of the heart, accompanied by systolic thrill. Systolic blood pressure was 140 mmHg. The chest X-ray showed evidence of severe cardiomegaly and pulmonary edema, compatible with congestive heart failure. The echodoppler examination demonstrated presence of severe mitro-tricuspid insufficiency and enlargement of the four cardiac chambers. Serial electrocardiographic examination revealed presence of first-degree atrioventricular block concomitant with occult ventricular pre-excitation. To the best of our knowledge, the combination of such different electrocardiographic abnormalities wasn’t reported before in a canine patient.